2003
DOI: 10.1074/jbc.m309555200
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Environment at the Active Site of Prolyl Oligopeptidase Is Highly Influential during Substrate Binding

Abstract: The positive electrostatic environment of the active site of prolyl oligopeptidase was investigated by using substrates with glutamic acid at positions P2, P3, P4, and P5, respectively. The different substrates gave various pH rate profiles. The pK a values extracted from the curves are apparent parameters, presumably affected by the nearby charged residues, and do not reflect the ionization of a simple catalytic histidine as found in the classic serine peptidases like chymotrypsin and subtilisin. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…In the case of the related prolyl oligopeptidase, the electrostatic environment of the active site region also considerably affected the pHrate profiles determined with various charged substrates. 13 ApAAP displays both exo-and endopeptidase activities, as well as sequence-dependent S1 specificity…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the related prolyl oligopeptidase, the electrostatic environment of the active site region also considerably affected the pHrate profiles determined with various charged substrates. 13 ApAAP displays both exo-and endopeptidase activities, as well as sequence-dependent S1 specificity…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was employed successfully for prolyl oligopeptidase, 23 but in another study the "inactive" enzyme hydrolysed the substrate. 13 Likewise, the substrate was cleaved during the lengthy crystallization period in the present investigation, so that only its acyl portion was seen in the crystal structure ( Figure 8). In the case of subtilisin modified similarly at the catalytic serine residue, an ∼10 6 -fold decrease in activity was demonstrated, indicating a small remaining activity, but with different mechanism not involving an acyl-enzyme intermediate.…”
Section: Hydrogen Bonds and Polar Contacts Between The A And B Molementioning
confidence: 98%
“…3 and Table1) mutations in the flexible loop structure markedly changed the catalytic power of POP resulting in orders of magnitude differences in activity. The pH-optimum of POP was also changed considerably, suggesting that mutations alter the catalytically relevant electrostatic interactions at the active site, which can markedly affect the binding and the route of the substrates to active site of POP [42]. A finely regulated functioning of the loop structure seems to be required for the mildly alkaline pH optimum of POP, at least with the neutral substrates like the short Z-Gly-Pro-BNA and the octapeptide.…”
Section: Crystal Structure Of the H680a Variant Reveals Cooperation Bmentioning
confidence: 99%
“…Crystal structures of prolyl oligopeptidase-substrate complexes from porcine muscle reveal that Arg involves itself in substrate binding by forming a hydrogen bond between the guanidine group and the main chain carbonyl group of the substrate (13). Arg 526 pulls the negatively charged substrate away from the catalytically competent position (4). Moreover, structure-based mutagenesis of the Myxococcus xanthus prolyl oligopeptidase has revealed that Arg 526 is involved in a salt bridge that acts as a latch for opening or closing the enzyme, and Arg 526 also helps to secure the incoming peptide…”
mentioning
confidence: 99%